Correlation of biochemical markers and inflammatory cytokines in autism spectrum disorder (ASD) - Ali Sabbah Noori; Parisa Rajabi; Javad Sargolzaei; Anita Alaghmand (BMC, 2024)
Abstract Introduction Autism Spectrum Disorder (ASD) is a disorder that severely affects neurodevelopment, and its underlying causes are not yet entirely understood. Research suggests that there may be a connection between the occurrence of ASD and changes in immune responses. This study aims to know if some biochemical and inflammatory cytokines are promising biomarkers for ASD and whether they are involved in the pathogenesis of ASD. Methods The serum levels of CRP, TNF-α, TGF-β, IL-1β, IL-10, 1 L-8, and IL-6 were measured in all of the patients (n = 22) and in the healthy (n = 12) children using ELISA method. Results The serum concentrations of IL-10 and IL-8 were significantly lower in the ASD patients compared to the control group (p < 0.05) and there were not significant differences between CRP, TNF-α, TGF-β, IL-6 and IL-1β levels in two groups. There were positive correlations between CRP and IL-10, also CRP and IL-8, in ASD group. In contrast to the ASD patients, the correlations of IL-8, IL-10, and CRP were not significant in the control group. Conclusion In conclusion, this study highlights the potential role of certain biochemical markers and inflammatory cytokines in ASD. Specifically, the lower levels of IL-10 and IL-8 in ASD patients, along with the significant correlations between CRP and these cytokines, suggest an altered immune response in individuals with ASD. These findings support the hypothesis that immune dysregulation may be involved in ASD pathogenesis. Further research is needed to explore these biomarkers and their mechanistic links to ASD, which could lead to improved diagnostics or therapeutic strategies.